Financing structure and bankruptcy risk in sharia commercial banks in Indonesia - Ruri Anggoro -; Aimatul Yumna (Financial Management Studies, 2021)
Purpose –The objective of examine the effect of the proportion level of profit-loss sharing financing to murabahah financing to the Islamic bank insolvency risk. Insolvency risk is measured by Zscore method Methodology–The samples of this study are 9 Islamic banks that consistenly published annual reports for OJK in the period 2011-2018. The data was analyzed using multiple linier regression model. Finding – The result show that the proportion level of profit-loss sharing financing to the non profit-loss sharing financing has no significant influence on islamic bank’s insolvency risk.